2023
DOI: 10.1021/acs.jmedchem.2c02124
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of CZS-241: A Potent, Selective, and Orally Available Polo-Like Kinase 4 Inhibitor for the Treatment of Chronic Myeloid Leukemia

Abstract: Recent studies demonstrate that PLK4 has emerged as a therapeutic target for the treatment of multiple cancers owing to its indispensable role in cell division. Herein, starting from previously identified effective compound CZS-034, based on rational drug design strategies, tyrosine kinase receptor A (TRKA) selectivity- and metabolic stability-guided structure–activity relationship (SAR) exploration were carried out to discover a highly potent (IC50 = 2.6 nM) and selective (SF = 1054.4 over TRKA) PLK4 inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In addition to hepatic metabolism, compounds will also be subject to degradation and modification by enzymes in plasma, particularly hydrolases and esterases . Hence, the plasma stability was also determined by incubating BWA-522 with mouse and human plasma at six different time points at 0, 15, 30, 45, 60, and 120 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to hepatic metabolism, compounds will also be subject to degradation and modification by enzymes in plasma, particularly hydrolases and esterases . Hence, the plasma stability was also determined by incubating BWA-522 with mouse and human plasma at six different time points at 0, 15, 30, 45, 60, and 120 min.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to hepatic metabolism, compounds will also be subject to degradation and modification by enzymes in plasma, particularly hydrolases and esterases. 61 Hence, the plasma stability was also determined by incubating BWA-522 with mouse and human plasma at six different time points at 0, 15, 30, 45, 60, and 120 min. The results are shown in Tables 8 and S2; BWA-522 remained ∼90% after a 120 min incubation, indicating that BWA-522 was highly stable in both mouse and human plasma.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Compound 1 (CFI-400945, IC 50 = 1.55 nM) has advanced into Phase II clinical trial but studies showed that it was not a selective PLK4 inhibitor. , To simplify the structure of CFI-400945, Yu et al utilized a scaffold hopping strategy to obtain compound 2 (YLT-11, IC 50 = 22 nM). , Compound 3 (centrinone or LCR-263) was developed by Oegema et al in 2015 with an IC 50 value of 2.7 nM, , and it was often used as a positive control. Recently, our research group reported three PLK4 inhibitors: Type-I inhibitors 4 (CZS-034, IC 50 = 0.2 nM) and 5 (CZS-241, IC 50 = 26 nM), Type-II inhibitor 6 (CZS-089, IC 50 = 26 nM). CZS-034 potently bound with PLK4 protein and exhibited stronger antiproliferation activity in TRIM37 -amplified breast cancer cells than CZS-241 and CZS-089.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Compound 3 (centrinone or LCR-263) was developed by Oegema et al in 2015 with an IC 50 value of 2.7 nM, 31,32 and it was often used as a positive control. Recently, our research group reported three PLK4 inhibitors: Type-I inhibitors 4 33 (CZS-034, IC 50 = 0.2 nM) and 5 34 (CZS-241, IC 50 = 26 nM), Type-II inhibitor 6 35 (CZS-089, IC 50 = 26 nM). CZS-034 potently bound with PLK4 protein and exhibited stronger antiproliferation activity in TRIM37-amplified breast cancer cells than CZS-241 and CZS-089.…”
Section: ■ Introductionmentioning
confidence: 99%
“…25 In our previous studies, centrinone showed poor liver microsomal stability ( t 1/2 = 5.8 min) and strong cytochrome P450 (CYPs) inhibition (Tables S1 and S2†), which suggested that its drug-like properties need to be further optimized. 29 In addition, centrinone contains nitrobenzene, resulting in a potential safety issue, which may be one of the reasons why it has not entered clinical research. Therefore, we hope to obtain novel, safe and effective small molecule PLK4 inhibitors through the structural modification of centrinone (Fig.…”
Section: Introductionmentioning
confidence: 99%